Pengaruh Agency Problem dan Inside Shareholdersterhadap Diversifikasi - Suwarni Suwarni; Elok Pakaryaningsih (Jurnal Riset Manajemen dan Bisnis, 2007)
This research qamines the effect of agenqt problem and inside shareholder on company's diversification poliqt. It is also intent to etcamine the effect of diversification on firm value and the ffict of inside shareholder on agency problern. The inside shareholder will be divided into two categories which are:managerial owhership and stock held by the company subsidiaries. The Herfindahl Index will be used to measure the lertel of diuersiJication, whilst the agency problem will be measured using the ratio of selling and general administrative cost. Moreover, the existence of compalry eJccess value derivefro* the company's diversification will be used to identify the firm value. Using the purposive random sampling method, the total sample drawn fro*.The Jakarta Stock Exchange fro* 2002 to 2005 are 160 companies with the accdption for companies within the financial sectors. Using multiple linear regression, the result shows positive and significant effect of agency problem on company's diversification policy. On the contrary, the result fail to demonstrate the ffict of diversification on firm value as well as the effect of inside shareholders on both agenq) problem and diversification. These findings suggest that the existence of agenqt problem is very subtle in Indonesia and the existence of inside shareholder is not intended to reduce theagency problemKeywords : Agency Pr ob I em, Ins ide Sharehol der, Div ers iJic ation